Prevalence of falls among older people attending a primary care clinic in Kuala Lumpur, Malaysia - S.G Sazlina; R Krishnan; A.S Shamsul; A Zaiton; R Visvanathan (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : The aim of this study was to determine the prevalence and the pattern of falls in community dwelling older people attending a primary care clinic in Kuala Lumpur, Malaysia. Methods : A cross sectional study was conducted in an urban primary care clinic. Participants aged 60 years and older were included in the study. A structured questionnaire, assessing socio-demographic variables, medical and falls history was administered by one investigator over a 3-month period in 2004. Results : A total of 151 respondents participated in this study with a response rate of 72%. The prevalence of falls was 47.0% over the previous 12-months period. Fifty-seven percent reported experiencing recurrent falls. Majority (61%) of falls occurred in the home and the two most common places were the bathroom (27%) and stairs (27%). Sixty-one percent of older people who fell, sustained an injury and most sought medical attention. Conclusion : In conclusion, falls are common amongst older people attending this primary care clinic. It occurred commonly in the home in the bathroom and near stairs. However, a larger local community study is warranted to determine the prevalence and risk factors for falls in Malaysia.